Punción seca metamórfica y su accion en punto gatillo miofascial del músculo trapecio de pacientes que asisten al centro de terapia fisiosport cantón Montalvo periodo septiembre 2017 a febrero 2018. - Verdezoto Nuñez, Marlon Jefferson (2018)
With the programmed scientific work, we sought to assess the influence of dry needling in the elimination of pain by trapezius muscle myofascial trigger point of patients attending the Fisiosport Canton Montalvo Therapy Center. To achieve this goal, the use of different methods derived from scientific research was required, both theoretical and empirical, processing the results obtained through the application of mathematical and statistical methods. The research deployed was framed in three stages, directly linked between, in the first and made an analysis of the existing conditions for its development, counting on the cooperation of Physician Physiatrist and a Master in Physiotherapy, in the second, after being selected applied techniques and methods, while in the third and final stage after the results were mathematically and statistically processed, the results were analyzed and discussed, and the conclusions and recommendations issued were also written. The research achieved results that, if taken into account by the relevant authorities, could, according to the experts' criteria, solve the assumed scientific problem, which would contribute to enhance the epistemology surrounding the subject matter of studies. Arriving the conclusion that dry needling positively influences the elimination of pain by myofascial trigger point of the trapezius muscle of the secretaries who attended in the period studied at the Fisiosport Therapy Center.